Body Composition Growth Patterns in Early Infancy: A Latent Class Trajectory Analysis of the Ethiopian iABC Birth Cohort. Issue 7 (30th May 2018) - Andersen, Gregers Stig; Wibaek, Rasmus; Kæstel, Pernille; Girma, Tsinuel; Admassu, Bitiya; Abera, Mubarek; Vistisen, Dorte; Jørgensen, Marit Eika; Michaelsen, Kim F.; Friis, Henrik; Wells, Jonathan C.K.
Abstract : Objective: The objective of this study was to identify subgroups with distinct fat and fat‐free growth patterns in the first 6 months of life and describe predictors of these different patterns. Methods: A total of 510 apparently healthy Ethiopian infants were followed from birth to 6 months of age. Each infant had at least three and up to six repeated measurements of fat and fat‐free mass using air‐displacement plethysmography. Latent class trajectory analyses were used to categorize infants in groups with distinct body composition patterns. Results: Four distinct fat mass and two fat‐free mass growth patterns were identified. Of the infants measured, 5% presented a delayed fat growth pattern and 3% presented a catch‐up fat growth pattern involving low birth weight but a significant fat growth velocity from 2.5 to 6 months. A large class had a high fat level at birth and an accelerated fat growth pattern in early infancy. Fat‐free growth was represented by two distinct classes with less variability. Catch‐up growth was primarily seen in fat mass. Conclusions: We identified distinct patterns of delayed, catch‐up, and accelerated fat growth in early infancy. This variability is not detected in regular anthropometric assessment and could be a mechanism linking early growth with later obesity and cardiometabolic risk.